Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/asna.200711135
|View full text |Cite
|
Sign up to set email alerts
|

On the detection of high‐frequency oscillations in short gamma‐ray bursts

Abstract: In this work we present the results of an investigation aimed at a search for an oscillatory phenomenon during short gamma-ray bursts. The wavelet technique, used for this analysis, is applied to the data from the BATSE 3B catalogue. We have detected oscillations, which periods are found to be in the milliseconds range and their amplitudes up to dozens of percents. A possible scenario for such a phenomenon is the coalescence of stellar-mass black holes and neutron stars. During the coalescence process the matt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…12 However, a period on the order of miliseconds is comparable to the QPO discovered in a short BATSE GRB (Zhilyaev & Dubinovska 2009), hence an inspiral inside the ISCO might, at least in some cases, lead to a QPO.…”
Section: Qposmentioning
confidence: 99%
See 1 more Smart Citation
“…12 However, a period on the order of miliseconds is comparable to the QPO discovered in a short BATSE GRB (Zhilyaev & Dubinovska 2009), hence an inspiral inside the ISCO might, at least in some cases, lead to a QPO.…”
Section: Qposmentioning
confidence: 99%
“…First searches for high-frequency QPOs were unsuccesful (Deng & Schaefer 1997;Kruger et al 2002), but Zhilyaev & Dubinovska (2009) employed a waveletbased approach to short BATSE GRBs, which yielded a QPO with a leading period of 5.5 ms in one case (trigger number 207), and a few chirping signals as well. NS-BH mergers are indeed expected to give rise to jet precession triggering the QPO modulation (Stone et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Another study by [5] utilized all Time-Tagged Event (TTE) data from BATSE, covering 2203 GRBs and 152 Soft Gamma-ray Repeaters (SGRs), employing Rayleigh power as an indicator to search for periodic signals and also found no evidence. Subsequent investigations used wavelet analysis for periodic signal searches [10]. Furthermore, a study using a Bayesian framework for period searches found no evidence for quasi-periodic oscillations (QPOs) in 44 bright SGRBs [11].…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have performed QPO searches in the main emission of SGRBs (e.g Kruger et al 2002;Zhilyaev & Dubinovska 2009;Dichiara et al 2013) and LGRBs (e.g., Kruger et al 2002;Cenko et al 2010;Guidorzi et al 2016;Tarnopolski & Marchenko 2021), where the former may originate from quasiperiodic jet precession from BH-NS mergers (Stone et al 2013), and the latter may be related to the long activity of the magnetars (Markwardt et al 2009). However, none of the claimed QPOs have been confirmed by further studies.…”
Section: Introductionmentioning
confidence: 99%